Mechanized tillage systems effects on soil erosion from an Alfisol in watersheds cropped to maize - Lal, R. (1985)
The effects of 6 years of continuous cultivation in 12 consecutive crops of maize (Zea mays) on changes in the physical and chemical properties of an Alfisol were investigated for two mechanized tillage systems imposed on twin watersheds of about 5 ha each. The tillage methods were no-tillage, with herbicides for weed control, and conventional plowing and harrowing. The soil organic matter content of the 0- to 10-cm layer of the no-tillage watershed increased by 7%, and that of the plowed watershed decreased by 72%. Soil pH declined by 0.3 and 1.7 units in no-tillage and plowed watersheds, respectively. As a consequence of pH changes, exchangeable cations declined with continuous cultivation, regardless of the tillage method, although the rate of decline was more drastic in the plowed than in the no-tillage watershed.